Overcoming Hoax: Prophet Muhammad's Strategies Integrated in PAI Teaching and Learning - Nasuki, Ahmad; Abu Bakar Askar, Romlah (Universitas Islam Indonesia, 2023)
The spread of false information, or hoaxes, occurs swiftly in cyberspace. Often, this widespread information has significant impact on people's lives. Unfortunately, hoaxes have targeted the youth, who represent the future generation. Therefore, it is of paramount importance for education to provide young students with comprehensive guidance on how to navigate and mitigate the impact of hoaxes. Hence, the objective of this study is to address hoaxes by examining the strategies employed by Prophet Muhammad and incorporating these strategies into Islamic Religious Education (PAI). The study employed a qualitative approach, specifically a literature review, to gather pertinent data related to the research. Primary and secondary sources were utilized as the data sources. Data analysis techniques involved condensing and evaluating the collected data, followed by the interpretation, conclusion, and verification of the selected data. The study's findings indicate that Prophet Muhammad employed four strategies to combat hoaxes: emotion management, discussion, broadening perspectives, and clarification. These strategies can be integrated into PAI, encompassing both curricular and extracurricular activities.